PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS BERBASIS WEB PADA DAYKLIN LAUNDRY - Anggreini, Novita Lestari; Ramdan, Dadan Saepul; Miliani, Fera (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
The purpose of this study is to analyse, design and also implement a Cash Receipt and Expenditure Information System at Dayklin Laundry Service Company. The research methodology uses descriptive methods and the data collection techniques used are field studies and library research data, the type of data uses quantitative and qualitative as well as secondary and primary data sources. The programming language used in this information system is web-based and MYSQL as the database. The system development method used is waterfall and system testing using black box. The information system that has been implemented functions as a system development from the use of simple bookkeeping to the desktop-based processing of cash receipts and disbursements. The function of this system is to overcome the problems that exist in Dayklin Laundry, among others, managing the calculation of cash receipts and disbursements and can maintain data security so that it is not known by all parties who have limited user access rights from this system, which are adjusted to the company policies. Based on the results of black box testing, the system, which is 98% up and running, is considered to be good.